ITRAQ-Based Proteomic Analysis of Ginsenoside F2 on Human Gastric Carcinoma Cells SGC7901. (18th October 2016) - Mao, Qian; Zhang, Pin-Hu; Yang, Jie; Xu, Jin-Di; Kong, Ming; Shen, Hong; Zhu, He; Bai, Min; Zhou, Li; Li, Guang-Fu; Wang, Qiang; Li, Song-Lin
Abstract : Ginsenoside F2 (F2 ), a protopanaxdiol type of saponin, was reported to inhibit human gastric cancer cells SGC7901. To better understand the molecular mechanisms of F2, an iTRAQ-based proteomics approach was applied to define protein expression profiles in SGC7901 cells in response to lower dose (20  μ M) and shorter duration (12 hour) of F2 treatment, compared with previous study. 205 proteins were screened in terms of the change in their expression level which met our predefined criteria. Further bioinformatics and experiments demonstrated that F2 treatment downregulated PRR5 and RPS15 and upregulated RPL26, which are implicated in ribosomal protein-p53 signaling pathway. F2 also inhibited CISD2, Bcl-xl, and NLRX1, which are associated with autophagic pathway. Furthermore, it was demonstrated that F2 treatment increased Atg5, Atg7, Atg10, and PUMA, the critical downstream effectors of ribosomal protein-p53 signaling pathway, and Beclin-1, UVRAG, and AMBRA-1, the important molecules in Bcl-xl/Beclin-1 pathway. The 6 differentially abundant proteins, PRR5, CISD2, Bcl-xl, NLRX1, RPS15, and RPL26, were confirmed by western blot. Taken together, ribosomal protein-p53 signaling pathway and Bcl-xl/Beclin-1 pathway might be the most significantly regulated biological process by F2 treatment in SGC7901 cells, which provided valuable insights into the deep understanding of the molecular mechanisms of F2 for gastric cancer treatment.